Clozapine prescription pattern in patients with schizophrenia in Asia: The REAP survey (2016). (May 2020) - Xu, Shi-Wei; Dong, Min; Zhang, Qinge; Yang, Shu-Yu; Chen, Lian-Yu; Sim, Kang; He, Yan-Ling; Chiu, Helen FK; Sartorius, Norman; Tan, Chay-Hoon; Chong, Mian-Yoon; Shinfuku, Naotaka; et al.
Highlights: Clozapine is an effective antipsychotic medication for treatment resistant schizophrenia and is widely used in some Asian countries. Regular surveys are useful to rationalize the prescription patterns of psychotropic medications in clinical settings. In total, 18.4% of schizophrenia patients received clozapine in Asian patients with schizophrenia, from 2.6% in Japan to 32.3% in Hong Kong. The clinical rationale of clozapine prescription needs careful consideration in Asia. Abstract: Clozapine is an effective antipsychotic medication for treatment resistant schizophrenia and is widely used in Asian countries. This study investigated clozapine prescription patterns and their associated factors in Asian countries and territories based on the database of the Research on Asian Psychotropic prescription study (REAP) conducted in 2016. Demographic and clinical information of 3744 schizophrenia patients in 15 Asian countries and territories was collected with a standardized data collection form. In total, 18.4% of the sample received clozapine, ranging from 2.6% in Japan to 32.3% in Hong Kong. Binary logistic regression analysis revealed that higher antipsychotic dose (OR = 1.002, P  < 0.001), less frequent first admission in the sample (OR = 0.6, P  < 0.001), more severe negative symptoms (OR = 1.4, P  = 0.001) and less first generation antipsychotics (FGAs) (OR = 0.2, P  < 0.001) were independently and significantly associated with clozapine prescription. Clozapine is frequently and increasingly prescribed for schizophrenia in Asia, with large variation across countries and territories. Given the diverse prescription patterns of clozapine found in Asian countries/territories, the clinical rationale of clozapine prescription needs careful consideration in Asia with more local input.